AEO: A plurilateral approach to mutual recognition - David Woddowson (Journal of Contemporary Economic and Business Issues, 2014)
This paper examines progress in establishing mutual recognition arrangements for Authorised Economic Operator (AEO) programs under the World Customs Organization's SAFE Framework of Standards to Secure and Facilitate Global Trade. In particular, it considers the likely impact on industry and customs administrations of the current bilateral approach to establishing mutual recognition agreements, and recommends a plurilateral approach that will minimise the proliferation of such agreements and, in doing so, reduce the regulatory burden on both administrators and the trading community.
Keywords: F10; F15; F33; 330; AEO; Mutual Recognition; Framework of Standards; Supply Chain Security